The Effect of Breathing Techniques During Labor on Pain Intensity in Mothers in the First Stage of Active Phase of Labor - Hanifah, Astin Nur; Wibowo, Markus (International Journal of Health Sciences, 2025)
Background: Labor pain is one of the main complaints experienced by mothers in labor, especially during the active phase of the first stage. Breathing techniques are a non-pharmacological method that can help reduce pain perception and increase comfort. Objective:To determine the effect of breathing techniques during labor on pain intensity in mothers in the first stage of labor in the active phase. Method:This study used a quasi-experimental design with a pretest-posttest control group design. The sample consisted of 40 mothers in the active phase of first-stage labor, divided into an intervention group (breathing techniques) and a control group (no intervention). Pain intensity was measured using a Visual Analog Scale (VAS). Data were analyzed using paired t-tests and independent t-tests. Results:The average pain score before intervention in the treatment group was 7.35 and after intervention it was 5.10 (p=0.000). In the control group, the pain score only decreased from 7.25 to 7.10 (p=0.421). An independent t-test showed a significant difference between the two groups (p=0.000). Conclusion:Breathing techniques effectively reduce the intensity of pain in mothers in the first active phase of labor.